Strategi Komunikasi Digital Yuki Anggia dalam Membangun Personal Brand di Instagram - Utami, Veronika Desi Ratna; Febriani, Erna (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to analyze the digital communication strategy carried out by a travel blogger Yuki Anggia in building a personal brand based on the concept of Mass self-communication associated with the eight laws of personal branding by Montoya and Vandehey through Instagram social media. To answer this problem, the researcher uses a post-positivism paradigm, with a qualitative approach. The research method used by the researcher is a type 3 case study by examining multiple cases and a single unit of analysis, with elements of communicator studies. The data source of this study was obtained through in-depth interview techniques with key informants and informants who will provide information to the researcher. The data collection technique used by the researcher is primary data obtained from observations of Yuki Anggia's Instagram content uploads and secondary data through literature that has discussed digital communication strategies and personal brands before. The theory used as a reference in analyzing Yuki Anggia's digital communication strategy is the concept of Mass self-communication by Manuel Castells. The focus of this study is how Yuki Anggia's digital communication strategy in building a personal brand on Instagram uses the concept of Mass self-communication based on self-generated, self-directed and self-selected aspects. The results of the study indicate that the research subjects have implemented the three elements of the digital communication strategy Mass Self-communication associated with the eight laws of personal branding. One finding is the personal value element contained in the self-generation element in building a positive image on their Instagram social media accounts. This research is expected to contribute to the implementation of digital communication strategies. Its relevance can be used as a guide for content creators and travel bloggers in improving their digital communication in building their personal brands.